2017
DOI: 10.1038/ncomms13905
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interplay between DNA repair and CRISPR/Cas9-induced DNA lesions at an endogenous locus

Abstract: The CRISPR–Cas9 system provides a versatile toolkit for genome engineering that can introduce various DNA lesions at specific genomic locations. However, a better understanding of the nature of these lesions and the repair pathways engaged is critical to realizing the full potential of this technology. Here we characterize the different lesions arising from each Cas9 variant and the resulting repair pathway engagement. We demonstrate that the presence and polarity of the overhang structure is a critical determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
187
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(203 citation statements)
references
References 47 publications
12
187
3
1
Order By: Relevance
“…A number of ‘alternative’ HDR pathways do not involve RAD51-mediated strand invasion [reviewed by (86)], among them HDR supported by SSO donors. At nicks, HDR by SSO donors requires RPA, but is stimulated dramatically (10-fold or more) upon depletion of RAD51 itself or factors that promote loading of RAD51 on DNA, including BRCA2 and its binding partners PALB2 and SHFM1; or by expression of the dominant negative RAD51K133R mutant or the inhibitory BRC3 peptide (9,10,87). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of ‘alternative’ HDR pathways do not involve RAD51-mediated strand invasion [reviewed by (86)], among them HDR supported by SSO donors. At nicks, HDR by SSO donors requires RPA, but is stimulated dramatically (10-fold or more) upon depletion of RAD51 itself or factors that promote loading of RAD51 on DNA, including BRCA2 and its binding partners PALB2 and SHFM1; or by expression of the dominant negative RAD51K133R mutant or the inhibitory BRC3 peptide (9,10,87). …”
Section: Discussionmentioning
confidence: 99%
“…The human hemogloblin beta (HBB) and delta (HBD) genes are homologous direct repeats of nearly identical sequence spaced 6 kb apart, reminiscent of the organization of target and donor sequences in the DR-GFP reporter. HDR at paired nicks targeted to the HBB gene was analyzed in human U2OS osteosarcoma cells (87) which provide a convenient model for studying targeted HDR although they do not express globin genes. Paired Cas9D10A or Cas9N863A nickases were targeted to sites spaced to generate ends 47 nt in length and bearing 5′ or 3′ overhangs respectively (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that different types of cuts engage different repair pathways, because 5' overhanging ends yield higher levels of HDR than 3' overhangs 5 . The fact that Trichostatin A and MLN4924 increase TNS with Cas9n and Cpf1 but has no effect with Cas9 suggests that blunt ends introduced by Cas9 may be repaired by different mechanisms versus 5' overhanging DNA ends introduced by Cpf1 or Cas9n.…”
mentioning
confidence: 99%
“…If the donor DNA provided in the experiment carries mutations, these will be introduced into the genome (precise genome editing). Repair with homologous ssDNA or dsDNA has been suggested to engage different pathways 5 . We will refer to Targeted Nucleotide Substitutions using ssDNA donors as 'TNS' and targeted insertion of cassettes .…”
mentioning
confidence: 99%
“…On the other hand, other repair pathways such as NHEJ, MMEJ, and single-strand annealing (SSA) are considerably active during the majority of the cell cycle. In addition, single-strand DNA (ssDNA) can also be incorporated at the DSB site via single-strand template repair (SSTR), which is thought to be independent from HR, because SSTR is not Rad51-dependent (Bothmer et al 2017;Richardson et al 2017). In this review, we summarize these HR-independent gene knock-in systems developed recently.…”
Section: Introductionmentioning
confidence: 99%